2007
DOI: 10.1063/1.2752769
|View full text |Cite
|
Sign up to set email alerts
|

Wet oxidation of nitride layer implanted with low-energy Si ions for improved oxide-nitride-oxide memory stacks

Abstract: To cite this version:V. Ioannou-Sougleridis, P. Dimitrakis, V.Em. Vamvakas, P. Normand, Caroline Bonafos, et al.. Wet oxidation of nitride layer implanted with low-energy Si ions for improved oxide-nitride-oxide memory stacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…The 10 years extrapolated memory window at room temperature is 1.7 V and 2.7 V for the Si and N-implanted samples respectively. The increased retention loss rate of this study as compared to previous [2] is attributed to the thinner initial ON structures and the increased ion implantation induced damage of the tunnel oxide.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The 10 years extrapolated memory window at room temperature is 1.7 V and 2.7 V for the Si and N-implanted samples respectively. The increased retention loss rate of this study as compared to previous [2] is attributed to the thinner initial ON structures and the increased ion implantation induced damage of the tunnel oxide.…”
Section: Resultscontrasting
confidence: 49%
“…An alternative method to accomplish significant advances in device performance is via low-energy silicon ion implantation into oxide nitride stacks followed by a low thermal budget wet-oxidation [2]. In addition, it has been shown that nitrogen low-energy implantation can also be utilized through a similar method to fabricate reliable modified ONO stacks [3].…”
Section: Introductionmentioning
confidence: 99%
“…High temperature annealing in inert ambient of the silicon implanted SiO 2 /Si 3 N 4 stacks result to the formation of a Si nanoparticle band (NP) within the nitride layer [5]. In contrast wet oxidation at a reduced temperature of the implanted stack forms a thick control oxide layer [6]. This work will present the bas electrical characteristics of the resulting stac attention to their memory properties.…”
Section: Introductionmentioning
confidence: 97%
“…Typical LE-IBS achievements are the formation of Si and/or Ge ncs within SiO 2 [5][6][7][8][9], Si 3 N 4 [10,11] and Al 2 O 3 [12]. In addition, LE-IBS has been successfully implemented for the low thermal budget production of the blocking oxide of silicon oxidenitride-oxide silicon (SONOS)-type memory structures by wet oxidation of Si-implanted Si 3 N 4 materials [13].…”
Section: Introductionmentioning
confidence: 99%